Development of superelastic SMA angles as seismic-resistant self-centering devices. (1st September 2020) - Wang, Bin; Zhu, Songye; Chen, Kaixin; Huang, Jiahao
Highlights: A novel type of superelastic SMA angles is developed as self-centering devices. Cyclic behavior of SMA angles was investigated for the first time. Satisfactory self-centering and energy dissipating capabilities were achieved. The FEM predictions agree with experimental results well. SMA angles can facilitate the realization of earthquake resilience. Abstract: Given their inherent unique superelasticity, the use of shape memory alloys (SMAs) to build seismic-resistant self-centering devices has presented attractive prospects in the field of earthquake resilience. This work investigates the mechanical behavior of superelastic SMA angles subjected cyclic loading. The deformation mechanism in superelastic SMA angles is elaborated first. Subsequently, experimental investigations of SMA angles are conducted using different loading protocols. Various mechanical properties, such as strength, self-centering and energy dissipation capabilities, are evaluated under varying loading amplitudes. Testing results show SMA angles can exhibit satisfactory flag-shaped hysteresis loops under multiple loading cycles. Different measures, such as the training process or the inclusion of reversed compressive cycles, can stabilize the hysteresis loops effectively and minimize the strength degradation and residual deformation in the repeated cycles. The cyclic behavior of the SMA angles is also simulated by using the finite element method to complement the observation and understanding obtained from the experiments. The proposed SMA angles are expected to offer an effective self-centering function to engineering structures toward earthquake resilience.